Potential Original Drug for Aspergillosis: In Vitro and In Vivo Effects of 1-N,N-Dimethylamino-5-Isocyanonaphthalene (DIMICAN) on Aspergillus fumigatus - Zsuzsa Máthéné Szigeti; László Tálas; Adrienn Széles; Zoltán Hargitai; Zsolt László Nagy; Miklós Nagy; Alexandra Kiss; Sándor Kéki; Gábor Szemán-Nagy (Journal of Fungi, 2022)
As the recent outbreak of coronavirus disease 2019 (COVID-19) has shown, viral infections are prone to secondary complications like invasive aspergillosis with a high mortality rate, and therefore the development of novel, effective antifungals is of paramount importance. We have previously demonstrated that 1-amino-5-isocyanonaphthalene (ICAN) derivatives are promising original drug candidates against Candida strains (Patent pending), even against fluconazole resistant C. albicans. Consequently, in this study ICANs were tested on Aspergillus fumigatus, an opportunistic pathogen, which is the leading cause of invasive and systematic pulmonary aspergillosis in immunosuppressed, transplanted and cancer- or COVID-19 treated patients. We have tested several N-alkylated ICANs, a well as 1,5-naphthalene-diisocyanide (DIN) with the microdilution method against Aspergillus fumigatus strains. The results revealed that the diisocyanide (DIN) was the most effective with a minimum inhibitory concentration (MIC) value as low as 0.6 µg mL−1 (3.4 µM); however, its practical applicability is limited by its poor water solubility, which needs to be overcome by proper formulation. The other alkylated derivatives also have in vitro and in vivo anti-Aspergillus fumigatus effects. For animal experiments the second most effective derivative 1-N, N-dimethylamino-5-isocyanonaphthalene (DIMICAN, MIC: 7–8 µg mL−1, 36–41 µM) was selected, toxicity tests were made with mice, and then the antifungal effect of DIMICAN was tested in a neutropenic aspergillosis murine model. Compared to amphotericin B (AMB), a well-known antifungal, the antifungal effect of DIMICAN in vivo turned out to be much better (40% vs. 90% survival after eight days), indicating its potential as a clinical drug candidate.